Screening for asymptomatic rheumatic heart disease: Understanding the mechanisms key to the diagnostic criteria - Herbst, Philip (SA Heart Journal, 2017)
This focussed review describes important problems experienced in the world of echocardiographic screening for asymptomatic rheumatic heart disease (RHD). It offers a critical appraisal of the screening criteria and their application and explores some of the fundamental principles underpinning the shortcomings of individual criteria. The author illustrates important mechanisms that underlie the morphological changes seen in RHD that must be accounted for if these criteria are to be rationalised and improved upon.